Clinical Profile and Outcome of Patients in Pediatric Intensive Care Unit in India - K. Maheswari; Neha Sharma (New Horizons in Medicine and Medical Research Vol. 11, 2022)
The aim of the present study was to describe the clinical profile and the outcome of our PICU patients, and also to highlight the probable modifications that can be done which will lead to better outcome of critically ill children. The principle objective of Pediatric critical care is not only to decrease the mortality, but also to restore the child who is suffering from a life threatening condition to health with minimum pain anxiety and complications and to provide comfort and guidance to the child’s family. This is a Hospital based, retrospective, descriptive study, in a tertiary care centre in puducherry, south India. Children admitted and treated in PICU in pediatric department from January 2019 - December 2019 in Sri venkateshwara medical college hospital and research center, Puducherry, were the participants. This study has shown respiratory illness and infectious diseases as the most common clinical profile observed. The outcome noted was, out 345 patients admitted to paediatric ICU, 303 (87.8%) were discharged. About 37 (10.7%) patients went against medical advice and 5 (1.4%) patients were referred at parents request. The study would like to recommend for further detailed prospective studies in future, with emphasis on the awareness of the most common and emerging rare etiology of patients admitted to PICU.